First record of Nemopalpus phoenimimos Quate & Alexander, 2000 (Diptera, Psychodidae, Bruchomyiinae) in Venezuela - Cazorla, Dalmiro (2014)
The moth fly (Diptera: Psychodidae) of the Bruchomyiinae subfamily Nemopalpus phoenimimos Quate & Alexander, 2000 is recorded for the first time in Venezuela. Two specimens were collected at 2200 m of altitude in Escagüey (8°42’31.19”N; 70°59’41.25”W), Mérida state, from Venezuelan Andes region. This record represents the second Nemopalpus Macquart, 1838 species reported from this country.